Factors Influencing the Use of Antibiotics among Adults in the Greater Accra Metropolis - Owusu-Asare, A.A. (University of Ghana, 2018)
Introduction: Antibiotic resistance is a global public health issue. Although antibiotic resistance will suffice naturally over time, increased use/misuse of antibiotics escalates the process. In Ghana there is a dearth of studies exploring the relationship between knowledge, attitude and practices on consumption of antibiotics by individuals within the community. The objective of this study was to determine the factors influencing antibiotic use among adults within the Greater Accra Metropolis in Ghana. Method: A cross-sectional analytical study design using interviewer-administered questionnaire was conducted in twenty communities of the Greater Accra Metropolis. A total of 470 participants were interviewed. The questionnaire assessed level of antibiotic use, knowledge and attitude towards antibiotic use and resistance. Descriptive analysis, bivariate and multivariate logistic regression using Stata version 15.0 was used to analyze the data. Results: Among the 470 respondents, 93.4% (n=439) had ever used antibiotics. The most commonly used antibiotic was Augmentin/Amoksiklav. About 71.1% (n=312) purchased the antibiotics with prescription, while 47.2% (n=207) of the respondents obtained their antibiotics from the hospital. About 27.3% (n=120) of the antibiotic users used the antibiotics to treat pain, toothache (16.2%, n=71), sore throat (14.1%, n=62), and fever (13.9%, n=61). The knowledge rating of respondents on antibiotic use and antibiotic resistance was about 90.0% with a mean score of 63.1% ± 13.9%. Majority (94.6%) of the respondents had good attitudes towards antibiotic use. The use of antibiotics was significantly associated with the age categories . Highest level of education and the employment status of the respondents were also both significantly associated with the use of antibiotics respectively. Area of residence and the insurance status of respondents also showed significant association with the use of antibiotics, respectively. Multivariate analysis showed that females were more likely than males to use antibiotics (AOR 1.53, 95% CI 0.64-3.65). Participants with tertiary level of education were more likely to use antibiotics compared to those with no education (AOR 8.35, 95% CI 0.54-128.72). Manual workers used more antibiotics compared to the unemployed (AOR 3.48, 955 CI 1.11-10.87). Highest level of education, area of residence and manual worker were significantly associated with antibiotic use (p<0.001, p < 0.001and p<0.032 respectively) Conclusion: The number of people using antibiotics is still high despite efforts by the Ministry of Health to educate the public on antibiotic use and resistance. Most of the respondents purchased the antibiotics using a prescription and used it to treat pain, a condition for which antibiotics is not medically indicated. Overall, many people however had good knowledge and attitudes towards duration and side effects of antibiotic use. Highest level of education and area of residence were significantly associated with the use of antibiotics.
Thesis (MPh)
Keywords: Antibiotics; Consumption; Interviewer-Administered; Augmentin/Amoksiklav